2014
DOI: 10.1073/pnas.1317731111
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3 inhibitors induce the canonical WNT/β-catenin pathway to suppress growth and self-renewal in embryonal rhabdomyosarcoma

Abstract: Embryonal rhabdomyosarcoma (ERMS) is a common pediatric malignancy of muscle, with relapse being the major clinical challenge. Selfrenewing tumor-propagating cells (TPCs) drive cancer relapse and are confined to a molecularly definable subset of ERMS cells. To identify drugs that suppress ERMS self-renewal and induce differentiation of TPCs, a large-scale chemical screen was completed. Glycogen synthase kinase 3 (GSK3) inhibitors were identified as potent suppressors of ERMS growth through inhibiting prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
133
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 38 publications
15
133
2
Order By: Relevance
“…A potential solution is to assess the dependence of particular sarcomas on more common targetable cancer pathways. In this regard, one recent development is the identification of aberrant Wnt/b-catenin signaling in synovial sarcoma models (68) and rhabdomyosarcoma (69). Combination targeted therapy again may have merit: a phase II trial of sorafenib and everolimus combination therapy achieved 45% 6-month progression-free survival (PFS; ref.…”
Section: Sarcoma Treatment: Current and Future Prospectsmentioning
confidence: 99%
“…A potential solution is to assess the dependence of particular sarcomas on more common targetable cancer pathways. In this regard, one recent development is the identification of aberrant Wnt/b-catenin signaling in synovial sarcoma models (68) and rhabdomyosarcoma (69). Combination targeted therapy again may have merit: a phase II trial of sorafenib and everolimus combination therapy achieved 45% 6-month progression-free survival (PFS; ref.…”
Section: Sarcoma Treatment: Current and Future Prospectsmentioning
confidence: 99%
“…This approach was useful for expansion of double transgenic primary tumors without the need for generating tumors within a syngeneic transgenic line. Our recent work has shown that cell transplantation approaches provide novel experimental models to assess ERMS drug sensitivity in vivo, where a single tumor can be expanded into thousands of animals and assessed for effects on growth, self-renewal, and neovascularization 15 . Moreover, we have successfully engrafted a wide range of tumors into rag2 homozygous mutant fish including T cell acute lymphoblastic leukemia, melanoma, and ERMS 23 .…”
Section: Discussionmentioning
confidence: 99%
“…7. Utilize engrafted fish for downstream applications including Fluorescence Activated Cell Sorting (FACS) to assess differentiation status (Figure 3H), standard histological analysis (Figure 3F), imaging therapy responses 15 , and/or serial transplantation approaches including limiting dilution analysis 11 .…”
Section: Transplantation Of Erms Into Adult Rag2 Homozygous Mutant Zementioning
confidence: 99%
See 1 more Smart Citation
“…Although most chemical screens described to date are using embryos less than 72 hpf, there are examples of chemical screens performed in older embryos up to 20 dpf with soaking technique. 34 Thousands of wildtype or genetically modified embryos can be obtained from a large mating, ideal for chemical screens, both genetic and phenotypic. 35 In a given genetic or disease model, a chemical suppressor screen can be performed in an attempt to reverse the phenotype or the genetic lesion, identifying new pathways of regulation in the pathophysiology of disease.…”
Section: Chemical Screens In Zebrafishmentioning
confidence: 99%